An Application of PLAR in the Development of the Aboriginal Self: One College’s Experience - Robertson, Lloyd Hawkeye (International Review of Research in Open and Distributed Learning, 2011)
Some forms of prior learning assessment and recognition (PLAR) invite self-reflection and the generation of new knowledge leading to self-growth in granting credit for past experiential learning. This paper examines the experience of a northern Canadian community college using PLAR portfolio development to assist in individual self-growth among people of aboriginal ancestry. The author reviews the theoretical underpinning behind the notion that PLAR may be used in identity construction and reviews some of the historical circumstances affecting the development of aboriginal selves. Divergent views of participants who had completed PLAR facilitator training on portfolio development are examined. Ethical concerns are raised, and guidelines are proposed for the use of PLAR in portfolio development and identity construction.